2023
DOI: 10.3389/fnut.2023.1204732
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial drivers influencing local food purchasing: beyond availability, the importance of trust in farmers

Valentina Carfora,
Patrizia Catellani

Abstract: IntroductionAlthough consumers bought more local food during the changing context of pandemic COVID -19, this positive modification may not become a stable habit afterward.MethodsTo understand this change in drivers of consumers' intention to buy local food, we investigated the role of perceptions of various intrinsic and extrinsic attributes of local food, its perceived quality, price and availability, and consumers' trust in local food producers. We also investigated the role of sociodemographic variables as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The foregoing findings addressing the potential barriers to the development of the local food market are reinforced by findings from a study by Carfora and Catellani ( 63 ), who identified availability as the most important element in local food decision-making. This is valid both in terms of seasonality and of space, as the possibilities differ in urban and rural settings.…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…The foregoing findings addressing the potential barriers to the development of the local food market are reinforced by findings from a study by Carfora and Catellani ( 63 ), who identified availability as the most important element in local food decision-making. This is valid both in terms of seasonality and of space, as the possibilities differ in urban and rural settings.…”
Section: Resultsmentioning
confidence: 94%
“…Farm gate sale seems to be organizationally simple and financially advantageous for both clients and sellers, moreover, the opportunity to visit farmers and see with their own eyes where their food comes from is very attractive for customers. This may be related to consumers’ need to obtain food from a trusted source, because as the study by Carfora and Catellani ( 63 ) states, trust is one of the three decisive factors (along with availability and health) motivating consumers to buy local food.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations